2012
DOI: 10.1038/nchembio.1043
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the genetic code of Drosophila melanogaster

Abstract: Genetic code expansion for unnatural amino acid mutagenesis has, until recently, been limited to cell culture. We demonstrate the site-specific incorporation of unnatural amino acids into proteins in Drosophila melanogaster at different developmental stages, in specific tissues and in a subset of cells within a tissue. This approach provides a foundation for probing and controlling processes in this established metazoan model organism with a new level of molecular precision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
155
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(159 citation statements)
references
References 24 publications
2
155
0
2
Order By: Relevance
“…ND, no data. mammalian culture cells, and plants (58)(59)(60)(61)(62). Similar translational switches can also be constructed using these pairs and can be easily implemented with applicable organisms.…”
Section: Discussionmentioning
confidence: 99%
“…ND, no data. mammalian culture cells, and plants (58)(59)(60)(61)(62). Similar translational switches can also be constructed using these pairs and can be easily implemented with applicable organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Carell and co-workers showed that a norbornenemodified Lys (68) can be genetically encoded into His 6 -tagged human polymerase κ, and that efficient labeling of polymerase κ can be accomplished with the nitrile imines generated from either the hydrazonyl chloride precursor or the corresponding tetrazole [23]. The utility of the norbornene modified amino acids was also demonstrated in the tetrazine ligation in eukaryotic cells by other research groups [46][47][48]. Smaller strained alkenes such as cyclopropene have also been developed for the photoclick chemistry.…”
Section: Site-specific Labeling Of Proteins Via the Photoinduced Tetrmentioning
confidence: 94%
“…This technology made it possible to photocontrol protein localization 45 , signal transduction 46,47 and gene expression 49 . This approach, demonstrated initially in mammalian cells, should rapidly benefit from the recent upgrade of the unnatural mutagenesis strategy to multicellular organisms 50 .…”
Section: Chemical and Genetic Hybrid Photoactuatorsmentioning
confidence: 99%